The Implementation of a Generative Learning Model With Contextual Approach Toward Physics Learning Outcomes - Parni, Nurul Hasanah; Akmam, Akmam (Department of Physics Universitas Negeri Padang, 2023)
Learning is an interactive process among students to accomplish the educational outcome. The problem occurring is that the students give few participations in during the learning process, since they only listen to the teachers, as a result, they are not able to develop their own knowledge so the learning outcome is low. The solution offered to improve the learning outcome is implement generative learning model which is based on contextual approach. The goal of the study is to discover the impact of generative learning model based on contextual approach toward the results of students learning about dynamic fluid material in the second grade of High School 13 Padang particularly science students. This is a quasi experiment research with Post-test Only Control Design. The population of this research is science students of High School number 13 Padang in the year of 2022/2023. The technique used to achieve data is Purposive Sampling. The sample is XI Science 1 students as experiment class and XI Science 3 as control group. The instrument applied is written test in form of multiple questions. Data analysis was done by mean similarity test. The result showed a significant variation between students learning outcome from the group which utilized generative learning model PBL. The average of student’s learning outcome in experiment group is 73.14 and control group PBL is 69.83. Based on the equality test two averages are obtained tcount 9.70 and ttable=1.995 in significant level alfa = 0,05. The H0 requirement refused is if ttable < tcount. The mark of tcount is in the denial of H0 hereby Hi is received. It proves that generative learning model based on contextual approach affected students learning outcome.